Analisis Molecular Docking Senyawa dari Jamur Endofit Bawang Dayak (Eleutherine bulbosa) Sebagai Inhibitor Lipase Pankreas - Frans Grovy Naibaho; Ebrry Dwi Putra; Desimaria Panjaitan4; Vinsen Willi Wardhana (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2022)
Nowadays some efforts are being made to reduce obesity by using drugs that aim to reduce appetite of the drug users. However, the use of drugs still has harmful side effects. Endophytic fungi originating from the Dayak onion plant are thought to have secondary metabolites that have potential as anti-obesity. The aims of this study were to determine the compounds produced by endophytic fungi of Dayak onion and to determine the potential components as inhibitors of pancreatic lipase enzymes. Samples of Dayak onions were collected from Palangka Raya using purposive sampling method. Isolation of endophytic fungi was conducted using surface sterilization method and the isolates were grown on PDA. Isolates were characterized and fermented on PDB for 14 days. The selected isolate was analyzed by using GCMS then molecular docking was performed using Autodock Vina and PyRx. The research results showed that there were 7 isolates of endophytic fungi isolated from leaves and roots tissues of Dayak onion. GCMS analysis showed that EBD1 contains 38 compounds. Molecular docking analysis showed that 1,3-Di-O-Acetylpentopyranose, a test ligand, has the closest binding affinity value (-6.6 kcal/mol) to orlistat (control) (-6.8 kcal/mol). Thus, it has the potential as an inhibitor of pancreatic lipase enzyme protein.